Global religious history and genealogical critique - Bergunder, Michael (AЯGOS, 2024)
Karénina Kollmar-Paulenz presents an approach to religious studies that combines source interpretation with critical theoretical reflection. She questions European dominance in defining religion and argues for a globalised, multicentric method that includes European and non-European perspectives on an equal footing. However, her approach still faces the challenge of decentralising Europe as the primary conceptual reference in this field.